Dietary supplement use of elite German athletes and knowledge about the contamination problem - Braun, H.; Koehler, K.; Geyer, H.; Thevis, M.; Schänzer, W. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Dietary supplement (DS) use is widespread in elite athletes. Mainly described motives for DS use are increasing performance, maintaining health or optimizing regeneration. (Braun et al., 2009) The benefits of most products are still unclear because their effectiveness is often not scientifically proven. In contrast, since 1999 the risk on DS for contaminations and adulterations with doping substances is well described (Geyer et al. 2008). Therefore, the aim of the study was to evaluate DS use in elite athletes and their knowledge about the contamination problem. Methods: During the preparation period (June-July 2008) for the Olympic Games 2008 in Beijing, we provided to 193 elite German athletes a closed-ended questionnaire to assess the past and present (DS use in the past 4 weeks) use of DS. Additionally, athletes have been asked about the contamination problem, motives of DS use, sources of advice, and supplement sources. The questionnaires were voluntarily returned by 117 (age 26.4 ± 5.8 y, male n = 74, female n = 43) athletes from 16 different sports. Results: Almost all athletes (97 %) have used DS in their active sports career, while 88 % reported a use (range 1-19) in the present period. For the group of DS users Minerals (74 %), vitamins (65 %), sport beverages (63 %) were most frequently used in the present period. Major motives for using supplements were optimizing regeneration (70 %), immune functions (64 %), health related (61 %) and increasing performance (48 %). Physicians (56 %), coaches (35 %), nutritionists (30 %) and physiotherapists (22 %) mainly recommended DS. Among all athletes, 63 % classified the contamination problem correctly (CCPC). However compared to the non-CCPC, this did not influence their supplement use according to frequency, motives, sources of advice, and supplement sources. Apart from that, the group of CCPC used more often individual nutrition consulting (p = 0.002) and felt better elucidated about usage of DS (p = 0.002). Discussion: The present data confirm the fact that DS use is widespread in elite athletes. Leading sport organizations recommend that: "athletes should be ensure they have a good diet before contemplating supplement use" (Maughan et al., 2007). However, only 54 % of the athletes ever had an individual nutrition consulting. Almost 2/3 of the athletes reported to be aware of the contamination problem. This is more than we found in young athletes (Braun et al., 2009). Anyway, it still seems necessary to educate athletes about risks and benefits of DS and include physicians, coaches, nutritionists and physiotherapist into this process.